Evaluation without monitoring: old methods, new approaches. Issue 2 (17th February 2022) - Blaser Mapitsa, Caitlin; Ramasobana, Mokgophana
ABSTRACT: The evaluation sector has been struggling with systems that claim to be monitoring and evaluation, but in fact stop with the monitoring. However, equally problematic, yet much less discussed, is the phenomenon of evaluation without monitoring. This article considers three different contexts that may require evaluators to evaluate a programme with little foundational monitoring data. It explores some of the underlying causes of this and suggests certain methods and approaches that are useful for evaluators to draw on in these situations.